HIV-negative male couples' attitudes about pre-exposure prophylaxis (PrEP) and using PrEP with a sexual agreement. Issue 8 (2nd August 2016) - Mitchell, Jason W.; Lee, Ji-Young; Woodyatt, Cory; Bauermeister, José; Sullivan, Patrick; Stephenson, Rob
ABSTRACT: One efficacious strategy to help prevent HIV is oral pre-exposure prophylaxis (PrEP), a daily regimen of antiretroviral treatment taken by HIV-negative individuals. Two of the recommendations of Centers for Disease Control and Prevention (CDC) guidelines for PrEP pertain to being in a relationship (i.e., male couples). Despite the recognition of how primary partners in male couples' relationships shape HIV risk and CDC's PrEP guidelines, there is a paucity of data that examine HIV-negative male couples' attitudes toward PrEP use and using PrEP with a sexual agreement. A sexual agreement is an explicit agreement made between two individuals about what sex and other related behaviors may occur within and outside of their relationship. In this qualitative study, we examine HIV-negative male couples' attitudes toward PrEP use and whether they thought PrEP could be integrated into a sexual agreement. Data for this study are drawn from couple-level interviews conducted in 2014 with 29 HIV-negative male couples who had a sexual agreement and were from Atlanta or Detroit. Both passive (e.g., flyers) and active (e.g., targeted Facebook advertisements) recruitment methods were used; the sample was stratified by agreement type. Thematic analysis was applied to identify the following themes regarding HIV-negative male couples' attitudes toward PrEP use: (1) PrEP and condom use; (2) concerns about PrEP (e.g., effectiveness, side effects, and promoting sexually risky behavior); and (3) accessibility of PrEP. Some thought PrEP could be a part of couples' agreement because it could help reduce sexual anxiety and sexual risk, and would help keep the couple safe. Others described PrEP use with an agreement as something for "others". Some were also concerned that incorporating PrEP could usurp the need for a sexual agreement in a couples' relationship. These themes highlight the need to improve informational messaging and promotion efforts about PrEP among HIV-negative male couples who may benefit from using it.